2018
DOI: 10.1016/j.bbagen.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylation is a post-translational modification of Alix regulating the membrane organization of exosome-like small extracellular vesicles

Abstract: Beyond its biological relevance, our study also provides the means for a comprehensive structural characterization of EVs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 67 publications
2
45
0
Order By: Relevance
“…These data confirmed that OMVs size did not vary in the temperature range investigated and no membrane damages were reported. However, the smooth peak centered at Q ≈ 1 nm −1 (inset of Figure 8a) is related to the thickness of the membrane and has been already detected by SAXS on Alix-positive exosome-like small extracellular vesicles (Romancino et al, 2018). This peak significantly changed the shape and moved towards higher Q values at increasing temperatures, although this variation was modest.…”
Section: Small Angle X-ray Scattering Experimentsmentioning
confidence: 59%
“…These data confirmed that OMVs size did not vary in the temperature range investigated and no membrane damages were reported. However, the smooth peak centered at Q ≈ 1 nm −1 (inset of Figure 8a) is related to the thickness of the membrane and has been already detected by SAXS on Alix-positive exosome-like small extracellular vesicles (Romancino et al, 2018). This peak significantly changed the shape and moved towards higher Q values at increasing temperatures, although this variation was modest.…”
Section: Small Angle X-ray Scattering Experimentsmentioning
confidence: 59%
“…The functions of EVs are strictly correlated to the cell phenotype . As a consequence, different applications require EVs from different cells and, therefore, the field of EVs cannot rely on a single cell line.…”
Section: Methods For Improvement Of Upstream Ev Yieldmentioning
confidence: 99%
“…Despite these findings, EV proteomics has proven to be challenging due to co-isolation of non-EV proteins such as lipoproteins during EV isolation, which can mask the presence of less abundant, but potentially physiologically important, EV proteins. Palmitoylation can target proteins to the membrane of EVs 22 , suggesting that palmitoylated proteins are enriched in EVs. However, a recent study that analyzed PTMs of exosomes in depth 23 was conducted using a conventional proteomics procedure, and in that case palmitoylation was not detectable because the thioester bonds were cleaved off during the sample preparation and the palmitoyl groups were lost.…”
Section: Introductionmentioning
confidence: 99%